2014
DOI: 10.1088/0004-637x/794/2/150
|View full text |Cite
|
Sign up to set email alerts
|

RELATIVE ASTROMETRY OF COMPACT FLARING STRUCTURES IN Sgr A* WITH POLARIMETRIC VERY LONG BASELINE INTERFEROMETRY

Abstract: We demonstrate that polarimetric interferometry can be used to extract precise spatial information about compact polarized flares of Sgr A*. We show that, for a faint dynamical component, a single interferometric baseline suffices to determine both its polarization and projected displacement from the quiescent intensity centroid. A second baseline enables two-dimensional reconstruction of the displacement, and additional baselines can self-calibrate using the flare, enhancing synthesis imaging of the quiescent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…We define the visibility domain polarimetric ratio and phase (following the notation of Johnson et al 2014)˜(…”
Section: Fundamentals Of Interferometric Imagingmentioning
confidence: 99%
“…We define the visibility domain polarimetric ratio and phase (following the notation of Johnson et al 2014)˜(…”
Section: Fundamentals Of Interferometric Imagingmentioning
confidence: 99%
“…Doeleman et al (2009b) and Fish et al (2009) then showed that EHT baselines can sensitively detect periodicities associated with these hot spots. Addressing more general circumstances, Broderick et al (2011) suggested that phase-referenced observations with the EHT may allow microarcsecond tracking of the image centroid on orbital timescales, and Johnson et al (2014) showed that polarimetric VLBI with the EHT is capable of microarcsecond astrometry of compact flaring structures, even for faint, non-periodic flares.…”
Section: Introductionmentioning
confidence: 99%
“…116 While this technique improves the image fidelity and dynamic range, it effectively averages out much of the information measured by the longest baselines as a trade-off. An interesting opportunity is that some of this variability may be dominated by a single blob of material accreting onto the BH, and one could in principle track such a "hot spot" over many orbits within a single observing run, using it as a test particle to probe the Kerr spacetime using both closure quantities and/or direct imaging 29,47,59,95 (see also §3.2). In addition to intrinsic source variability, the refractive substructure of ISM inhomogeneities impose an apparent time variability (with a characteristic timescale of about one day).…”
Section: Shadow Measurement Accuracy and Interferometric Simulationsmentioning
confidence: 99%